Effects of mean platelet volume, mean corpuscular hemoglobin concentration and neutrophil-to-lymphocyte ratio on mortality in patients undergoing coroner artery bypass graft surgery: Hematological parameters in coronary artery graft surgery - Güven , Cengiz; Doğukan , Mevlüt; Demirci , Çiğdem; Üçkardeş , Fatih (Journal of Surgery and Medicine, 2023)
Background/Aim: Laboratory tests play a vital role in diagnosing, monitoring, treating, and determining the prognosis of diseases. Several parameters, including mean corpuscular hemoglobin concentration (MCHC), mean platelet volume (MPV), mean corpuscular volume (MCV), platelet distribution width (PDW), platelet count (PLT), plateletcrit (PCT), neutrophil count (NEU), platelet/lymphocyte ratio (PLR), and neutrophil/lymphocyte ratio (NLR), have been investigated in various diseases. This study aims to explore whether these parameters can predict mortality in patients undergoing coronary artery bypass graft surgery (CABG). Methods: The study was conducted as a retrospective cohort study, analyzing 2478 patients who underwent CABG in the cardiovascular surgery clinic of our hospital between January 2013 and November 2020. Preoperative blood count parameter values (PLT, PCT, PDW, MPV, MCHC, MCV, PLR, NEU, NLR, and MCHC/MCV) were compared between 80 patients who died after the operation (Group 1) and 80 patients who were discharged from the hospital (Group 2). Results: The analysis revealed that PLT and MCV were significantly lower in Group 1, while MPV, NEU, NLR, and MCHC/MCV were significantly higher. In the receiver operating characteristic (ROC) analysis, the positive probability rate of PLT in predicting mortality (cut-off >260.2, +LR: 2.44, 95% CI: 0.605–0.754) was higher than that of MPV (cut-off ≤7.53, +LR: 2, 95% CI: 0.584–0.735), MCV (cut-off ≤ 82.21, +LR: 1.26, 95% CI: 0.513–0.671), NEU (cut-off ≤68.2, +LR: 2.03, 95% CI: 0.640–0.785), NLR (cut-off ≤2.66, +LR: 2.58, 95% CI: 0.571–0.724), and MCHC/MCV (cut-off ≤0.4, +LR: 1.45, 95% CI: 0.551–0.706). Conclusion: Preoperative PLT, MCV, MPV, NEU, NLR, and MCHC/MCV values are effective parameters for predicting mortality in CABG patients.